Researches in the artificial insemination of pigs. Farrowihn rate of pigs inseminated once or twice in the same Oestrus: - ΕΛΕΥΘΕΡΙΟΥ ΕΛΕΥΘΕΡΙΟΣ Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
By the present study the following points have been examined: 1. The characteristiques of semen taken from seven boars, which are as follow: Volume, 200- 422ml. Viability motility 65/4, 2 to 70-/4,4. Density, 156 to 249xl06 spermatozoa/ml. Total sperm per ejaculate, 33,9 to 60,3xlO9. 2. A method to estimate the concentration of semen was adapted for the boar’s semen by using a photometer. 3. The farrowing rate of pigs inseminated once or twice in the same oestrus were 63,8 and 82,7% and the litter size 10,65 and 11,37 respectively.